Islamic educational thought in Indonesia: study of Azyumardi Azra’s thought - Jaffary Awang,; Nuriz, M. Adib Fuadi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Globalisation transformed Islamic education. In Indonesia, Islamic education contributed remarkably towards national growth. Nevertheless, it is not simple to accomplish the Islamic education goal due to its problem with the concept and method. This article examined the current Islamic educational thought, according to Azyumardi Azra. It studied the relevant literature and engaged it based on critical content analysis. The research discovered that Azyumardi Azra believed Muslims could meet the needs of modernity only by integrating the classical model of Islamic education and modern Western education. It is imperative to be administered so that Islamic education is more comprehensive, liberal, and democratic. His critics argued that modernisation of Islamic education established by Azyumardi Azra liberalised Islamic thought towards religious pluralism in Islamic education in Indonesia.